Peran pustakawan dalam membangun komunikasi interpersonal efektif pada layanan tandon di perpustakaan IAIN Kudus (Kajian perspektif Joseph A. Devito) - Buwana, Radiya Wira (Program Studi Diploma Tiga Ilmu Perpustakaan Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2025)
Background of the Study: Effective interpersonal communication between librarians and users is one of the factors that support the creation of excellent library services Objectives: This research was aimed to examine the role of librarians in building the effective interpersonal communication in the reserve collection service at the IAIN Kudus Library Method: This study was conducted using a qualitative descriptive research method. The data collection method used in this study was using the interview method, observation, and literature study. The data obtained in this study were then analyzed using the theory of effective interpersonal communication from Joseph A. DeVito Finding: The results of this study indicate that the role played by librarians in building effective interpersonal communication is to provide complete service information, provide motivation to users, provide services regardless of social and physical status, give praise to users, position themselves as partners, always be there when needed by users, and be able to accept suggestions and criticism from users. The results of the study indicate that the role played by librarians has fulfilled the five elements of effective interpersonal communication from Joseph A. DeVito. The five elements are elements of openness, empathy, supportive attitude, positive attitude, and equality Conclusion: From the results of this study, it can be concluded that librarians in the reserve collection service at the IAIN Kudus Library are able to build effective interpersonal communication with the users they serve